A Deconstructive Reading of the Trauma in Martin Aleidas Tanpa Pelayat dan Mawar Duka - Lany Kristono (Journal of Language and Literature, 2015)
Being one of the most widely discussed turmoil, the 1965 tragedy must have left a cultural trauma to those involved, particularly the victims. As one victim of the event, Martin Aleida should know better how such a trauma represents itself. Therefore, this study would like to examine the trauma in his work Tanpa Pelayat dan Mawar Duka (Without Mourners nor Roses): who suffers from the trauma, how they respond to the trauma, and the ideology underlying the trauma from the perspective of Deconstruction. Derridas Deconstruction has been selected as the story contains paradoxes and this study adopts Jeffrey Alexanders belief that trauma is socially constructed instead of a result of the event itself. A scrutiny of the trauma in the story confirms Alexanders notion of the trauma and the dominant ideas of the ruling class, including gender power relations, which shape the characters attitudes towards their trauma and their interactions. The findings also reflect the solidity of gender power relations.